Mapping socioscientific issues research in science education: Trends, pedagogy, competencies, and gaps (2021-2025) - Rifat Shafwatul Anam; Ahmad Yani (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2026)
Amid increasing global challenges characterized by uncertainty, complexity, and ethical dilemmas, socioscientific issues (SSI) have emerged as a critical framework for advancing science education. This study systematically examines research trends, pedagogical approaches, competencies, and research gaps in SSI studies. A systematic literature review (SLR) was conducted using the PRISMA protocol on 53 open-access articles published between 2021 and 2025 in selected high-impact Scopus Q1 journals. The findings reveal a growing concentration of SSI research within the selected corpus, particularly in recent publications. Qualitative approaches dominate, with studies largely situated in secondary and higher education contexts. Research primarily focuses on environmental and health-related issues, while argumentation, inquiry-based learning, and discussion are the most frequently applied pedagogical approaches. SSI-based learning fosters multidimensional competencies across cognitive, epistemic, and affective domains. However, key gaps persist, including limited thematic diversity, underrepresentation of primary education, insufficient integration of emerging technologies, and a lack of large-scale and longitudinal designs. This study underscores the need for broader implementation, methodological diversification, and technology integration. Limitations related to the bounded corpus and open-access selection are acknowledged, which may affect generalizability.